2009
DOI: 10.4103/0019-5154.55630
|View full text |Cite|
|
Sign up to set email alerts
|

Serum mucosa-associated epithelial chemokine in atopic dermatitis : A specific marker for severity

Abstract: Background:Mucosa-associated epithelial chemokine (MEC; CCL28) is considered pivotal in mediating migration of CCR3 and CCR10-expressing skin-homing memory CLA+ T cells. CCL28 is selectively and continuously expressed by epidermal keratinocytes, but highly upregulated in inflammatory skin diseases such as atopic dermatitis (AD).Aims:This controlled longitudinal study was designed to evaluate the expression of CCL28 serum levels in childhood AD and bronchial asthma (BA) and its possible relations to disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Various inflammatory cells, including both T cells and eosinophils expressing cutaneous lymphocyte‐associated antigen (CLA), CD4+ or CD8+, play an important role in initiating and progressing inflammatory reactions in AD tissue 1 . It has been shown that various cytokines and chemokines are involved in inflammatory‐cell infiltration into the lesion, and that their receptors are expressed on inflammatory cells or keratinocytes 2–5 . Colantonio et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various inflammatory cells, including both T cells and eosinophils expressing cutaneous lymphocyte‐associated antigen (CLA), CD4+ or CD8+, play an important role in initiating and progressing inflammatory reactions in AD tissue 1 . It has been shown that various cytokines and chemokines are involved in inflammatory‐cell infiltration into the lesion, and that their receptors are expressed on inflammatory cells or keratinocytes 2–5 . Colantonio et al.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been shown that various cytokines and chemokines are involved in inflammatory-cell infiltration into the lesion, and that their receptors are expressed on inflammatory cells or keratinocytes. [2][3][4][5] Colantonio et al 6 showed that expression of CCL1 and CCL18 is higher in atopic skin than in normal or pruritic skin. It has been documented that the secretion of the chemokine RANTES (regulated upon activation, normal T-cell expressed and secreted) is increased by antigens or staphylococcal enterotoxin B in peripheral monocytes in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…First, high levels of CCL28 have been identified in the sputum and airways of humans with asthma (8,9). Second, the receptors for CCL28, CCR3, and CCR10 are expressed on eosinophils, Th2 cells, iNKT cells, and regulatory T cells, all cell types that have been associated with asthma and atopic disease (9 -14).…”
mentioning
confidence: 99%
“…This result is consistent with the finding that CCL28 mRNA can be detected within normal and asthmatic lungs [ 35 ]. Although there is no evidence indicating increased CCL28 expression in asthmatic patient-derived lung tissue, a previous study reported that serum CCL28 levels in children with bronchial asthma are significantly higher than those in controls [ 9 ]. Therefore, this finding raises the possibility that CCL28 might stimulate the migration of circulating SSEA-1 + cells highly expressing CCR10 from the BM reservoir into the circulation, which then migrate into inflamed lung tissue via the CXCL11–CXCR7 axis.…”
Section: Discussionmentioning
confidence: 99%